Sex Differences in the Determinants of Fibrinolytic Activity - MacCallum, P. K.; Cooper, J. A.; Howarth, D. J.; Meade, T. W.; Miller, G. J. (Thrombosis and Haemostasis, 1998)
Impaired whole blood fibrinolytic activity (FA), measured by the dilute clot lysis time (DCLT), is associated with first episodes of ischaemic heart disease (IHD) in the Northwick Park Heart Study in men, especially under 55 years, and in women. In a community-based study to investigate possible determinants of the DCLT, and therefore to assess which fibrinolytic components might be predictors of first IHD events, we measured fibrinolytic variables in a sub-sample of 150 healthy adults (73 males, 77 females) randomly selected from a single general practice.Most of the variance in DCLT (68% in men, 63% in women) was explained by tissue-type plasminogen activator (t-PA) and plasminogen activator inhibitor type-1 (PAI-1) activities. In multiple regression analysis there was a significant difference in the strength of the association of t-PA activity with DCLT in men compared to women (test for interaction p = 0.05), the association of t-PA activity with DCLT being significant in males but not in females. Plasma PAI-1 activity was strongly associated with DCLT in both sexes. There was no independent association of DCLT with plasma fibrinogen, t-PA antigen, other fibrinolytic inhibitors, body mass index, serum lipids or C-reactive protein.Plasma PAI-1 activity in females and both t-PA and PAI-1 activities in males are the main determinants of whole blood FA measured by DCLT. It is therefore likely that these modulators of the plasma fibrinolytic system are associated with the onset of first clinical episodes of IHD. Elevated levels of t-PA antigen were positively associated with DCLT after adjustment for age and sex and therefore indicate impaired rather than enhanced FA. Further studies of the association of FA with risk of IHD should include not only “global” measures but also assessment of t-PA and PAI-1 activities, particularly as our results suggest that their associations with IHD may differ in men and women.